A Blockchain-Based Traceability System To Mitigate Counterfeit Cosmetics In E-Commerce: Proposed Model And Experimental Validation - Dinh Thien Tri; Hoang Gia Han; Phan-Anh-Huy Nguyen (Politeknik Negeri Batam, 2026)
The rapid expansion of e-commerce has intensified the proliferation of counterfeit cosmetics, posing serious risks to consumer health and brand integrity, particularly in emerging markets such as Vietnam. While blockchain-based traceability has been studied extensively, existing solutions rarely integrate dual-layer verification, privacy-preserving mechanisms, and hybrid off-chain storage into a cohesive, experimentally validated prototype. This paper proposes VeriGlow, a blockchain-based decentralized application (DApp) that delivers transparent, tamper-proof, and user-verifiable traceability for cosmetic products throughout the supply chain. The system integrates: (1) Ethereum smart contracts written in Solidity ^0.8.0 with structured functions including createProduct, transferOwnership, and getProductJourney for immutable lifecycle management; (2) a hybrid IPFS-on-chain storage model using Pinata-hosted Content Identifiers (CIDs) to synchronize off-chain media assets with on-chain metadata, significantly reducing gas consumption; (3) a dual verification mechanism combining dynamic QR codes with physical Batch IDs to prevent QR cloning and relay attacks; and (4) a privacy-preserving historySnapshot mechanism that selectively conceals intermediate ownership records from public view while retaining full on-chain auditability. A functional prototype was developed using Solidity, Web3.js, and MetaMask and validated against six test scenarios on the Ethereum Sepolia testnet and Ganache local network. Experimental results demonstrate product creation gas costs in the range of 245,000–310,000 gas units (approximately 0.0014–0.0018 ETH), ownership transfer costs of 58,000–72,000 gas units (approximately 0.0008 ETH), and zero-cost read operations, comparing favorably with prior Ethereum-based traceability systems. Transaction confirmation times averaged 5–7 seconds for creation and 3–5 seconds for transfers on the local network. All six test scenarios passed with 100% success rate across ten repeated executions. These findings validate VeriGlow as a technically feasible and practically applicable solution for combating counterfeit cosmetics in e-commerce environments and offer a replicable framework for blockchain-based traceability in similar high-risk consumer sectors.